Stosunki Unii Europejskiej z Ukrainą w kontekście europejskiej polityki sąsiedztwa - Olipra, Łukasz (The EU-Ukraine Relations in the Context of the European Neighbourhood Policy, 2007)
Beginning of the EU-Ukraine relations is dated on December 1991, when the Ukrainian society in referendum decided on entire independence of the country. The first reaction of the European Communities was declaration in which democratic character of referendum has been stressed. In 1998 the European Union and Ukraine signed the Partnership and Co-operation Agreement, which established institutional framework of mutual relations. The EU enlargement in 2004 caused a new situation for both parties. It is the first time in their history when the EU shares its border with Ukraine. To avoid the emergence of new dividing lines between enlarged EU and its neighbours the European Neighbourhood Policy was developed in May 2004. The aim of this article is to present the consequences of establishing the ENP for the EU--Ukraine relations. The first part presents the concept of the European Neighbourhood Policy, its origin, aims and instruments. Then the EU-Ukraine relations have been described with special stress on European context of "Orange Revolution". The next part of the article is an attempt to answer how the European Neighbourhood Policy has influenced EU-Ukraine relations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 291-304